Pengembangan Media Power Point Interaktif Berbasis Aplikasi Lumi Education pada Mata Pelajaran Fikih di MAS Darul Makmur Sungai Cubadak - Silfi Silfi; Puti Andam Dewi (Lembaga Yasin AlSys, 2026)
The development of interactive technology-based learning media in Islamic Religious Education has received attention in several studies, but research that specifically discusses the development of interactive PowerPoint media based on the Lumi Education application for the Fikih subject on the provisions of Hajj and Umrah worship in Madrasah Aliyah remains limited. This study aims to develop interactive PowerPoint media based on the Lumi Education application and determine the levels of validity, practicality, and effectiveness of the media in the Fikih subject for grade X students at MAS Darul Makmur Sungai Cubadak. This study employed a Research and Development (R&D) approach with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The research participants consisted of media expert validators, material experts, language experts, Fikih teachers, and grade X students of MAS Darul Makmur Sungai Cubadak, who were selected using purposive sampling. Data were collected through observation, interviews, validation sheets, and practicality and effectiveness questionnaires and were then analyzed using quantitative descriptive and qualitative descriptive analysis. The results showed that the interactive PowerPoint media based on the Lumi Education application was categorized as highly valid, highly practical, and highly effective in supporting the Fikih learning process. These findings contribute to the development of multimedia learning theory and interactive learning and broaden understanding of the development of technology-based learning media in Islamic Religious Education. The conclusion of this study affirms the importance of using interactive learning media to improve students’ motivation, attention, and understanding during the learning process.